Geotail observation of counter directed ESWs associated with the separatrix of magnetic reconnection in the near‐Earth magnetotail. Issue 1 (8th January 2014) - Li, S. Y.; Omura, Y.; Lembège, B.; Deng, X. H.; Kojima, H.; Saito, Y.; Zhang, S. F.
Abstract [1] A sub‐Alfve´nic jet in the tailward outflow region near the separatrix of the magnetic reconnection is observed by Geotail on 9 February 1995. Several dozens of electrostatic solitary waves/pulses (ESWs) are observed, respectively, on the current sheet‐side and the lobe‐side of the separatrix. The ESWs on the current sheet‐side are of type‐B with direction outward (toward to the tailward) while on the lobe‐side they are of type‐A directed to X‐line. The amplitude of ESWs on the current sheet‐side is about 6 times more than those on the lobe‐side, suggesting that energies flowing outward from the reconnection X‐line are much larger than those flowing inward. Moreover, observations show, that electron beams associated with ESWs, which are parallel to the ambient magnetic field, are much stronger on the current sheet‐side than on the lobe‐side of the separatrix. Furthermore, the direction of the electron beam on the lobe‐side of the separatrix is mainly antiparallel to the ambient magnetic field and it is mainly parallel on the current sheet‐side. Both are consistent with the propagation of ESWs which is in agreement with the generation mechanism of ESWs, which is suggested to be related to electron beams. These results are helpful for solving the issue of ESWs' generation mechanism associated with magnetic reconnection. It also provides an important clue for understanding the fast energy release during the magnetic reconnection process.